2022
DOI: 10.1002/cam4.4721
|View full text |Cite
|
Sign up to set email alerts
|

Predicting breast cancer risk in a racially diverse, community‐based sample of potentially high‐risk women

Abstract: Background: Identifying women with high risk of breast cancer is necessary to study high-risk experiences and deliver risk-management care. Risk prediction models estimate individuals' lifetime risk but have rarely been applied in community-based settings among women not yet receiving specialized care.Therefore, we aimed: (1) to apply three breast cancer risk prediction models (i.e., Gail, Claus, and IBIS) to a racially diverse, community-based sample of women, and (2) to assess risk prediction estimates using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Many studies have shown that the IBIS model, compared to the Gail and Claus models, is able to identify the highest percentage of the population at high risk [38][39][40][41].…”
Section: Tyrer-cuzick/ibis Modelmentioning
confidence: 99%
“…Many studies have shown that the IBIS model, compared to the Gail and Claus models, is able to identify the highest percentage of the population at high risk [38][39][40][41].…”
Section: Tyrer-cuzick/ibis Modelmentioning
confidence: 99%
“…Breast cancer is a life threatening malignancy that affects one in every eight women worldwide as stated by recent epidemiological statistics [1]. The high predicted global cancer statistics (12.5%) has put breast cancer as the second leading cause of cancer mortality in women with approximately 700,000 deaths in 2020 [2]. This emphasizes that much more efforts need to be allocated to understand the molecular events associated with breast cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%